Impacts of university lecturers demographic characteristics on their psychosocial work hazards - Christian S. Ugwuanyi (Universitas Negeri Padang, 2023)
There are a number of psychological risks associated with work for the majority of workers, and lecturers in particular. Nigerian workplaces are known to present psychosocial dangers, however, no studies have examined how the lecture attributes may affect these risks. In order to determine whether demographic factors can affect psychological workplace risks of academics, researchers examined factors such as age, education, and location of the university. A sample of 185 lecturers from universities in southeast Nigeria participated in the study, which utilized a qualitative research strategy and an ex-post facto research design. The study's data were collected using an adapted Copenhagen Psychosocial Questionnaire. A reliability index of 0.87 was calculated for the survey items. In order to analyze the data, we applied the statistical procedure called analysis of variance. While lecturers' ages and university location affected their psychosocial occupational hazards, their educational qualification did not play a significant role. As a result, lecturers are more likely to experience psychological workplace risks as they grow older. It is recommended that University authorities should consider the age of candidates when making their hiring decisions in order to avoid recruiting lecturers more likely to suffer psychological hazards.